Pengembangan Kemampuan Public Speaking dan Kepercayaan Diri Peserta Didik Madrasah Aliyah di Aceh - Hasanuddin, Hasanuddin; Rijal, Fakhrul (Jurnal Ilmiah Guru Madrasah, 2025)
Public speaking ability has become an essential skill in the digital transformation era, particularly in Islamic educational institutions. This study aims to analyze the strategies for developing public speaking skills and their impact on students' self-confidence at MAN 1 Banda Aceh and MAN 4 Aceh Besar. The research employs a qualitative descriptive-comparative approach through direct observation, in-depth interviews with school principals, vice principals for student affairs, public speaking trainers, and students, as well as institutional documentation. The findings indicate that both madrasahs implement systematic strategies encompassing initial assessment, goal setting, curriculum development, activity implementation, evaluation and feedback, reinforcement, supporting facilities, visual media utilization, emotional support, and peer collaboration. Four methods are applied: manuscript, memorization (memoriter), impromptu (spontaneity), and extemporaneous (outline elaboration). The implementation of public speaking training significantly impacts students' self-confidence, demonstrated through four aspects: confidence in one's own abilities, capability to make independent decisions, positive self-perception, and courage to express opinions to others. This study concludes that well-structured public speaking development strategies effectively enhance students' self-confidence and communication skills, preparing them to face competitive challenges in the future. The comparative findings reveal that both institutions share similar approaches while maintaining their respective institutional contexts, indicating that program success is determined more by implementation quality and consistency rather than specific organizational models. Abstrak Kemampuan public speaking telah menjadi keterampilan esensial di era transformasi digital, khususnya di lembaga pendidikan Islam. Penelitian ini bertujuan menganalisis strategi pengembangan kemampuan public speaking dan dampaknya terhadap kepercayaan diri peserta didik di MAN 1 Banda Aceh dan MAN 4 Aceh Besar. Penelitian menggunakan pendekatan kualitatif deskriptif-komparatif melalui observasi langsung, wawancara mendalam dengan kepala madrasah, wakil kepala bidang kesiswaan, guru pelatih public speaking, dan peserta didik, serta dokumentasi institusional. Hasil penelitian menunjukkan bahwa kedua madrasah menerapkan strategi sistematis yang mencakup penilaian awal, penetapan tujuan, pengembangan kurikulum, pelaksanaan kegiatan, evaluasi dan umpan balik, penguatan, fasilitas pendukung, penggunaan media visual, dukungan emosional, dan kolaborasi sesama. Empat metode diterapkan: manuskrip, hafalan (memoriter), spontanitas (impromptu), dan menjabarkan kerangka (ekstemporer). Implementasi pelatihan public speaking berdampak signifikan terhadap kepercayaan diri peserta didik, yang ditunjukkan melalui empat aspek: yakin pada kemampuan sendiri, mampu mengambil keputusan sendiri, mempunyai rasa positif pada diri, dan berani menyatakan pendapat kepada orang lain. Penelitian ini menyimpulkan bahwa strategi pengembangan public speaking yang terstruktur dengan baik efektif meningkatkan kepercayaan diri dan kemampuan komunikasi peserta didik, mempersiapkan mereka menghadapi tantangan kompetitif di masa depan. Temuan komparatif mengungkapkan bahwa kedua institusi memiliki kesamaan pendekatan dengan konteks institusional masing-masing, mengindikasikan bahwa keberhasilan program lebih ditentukan oleh kualitas implementasi dan konsistensi pelaksanaan daripada model organisasional spesifik.